Ultra-Broadband Sound Absorbing Materials Based on Periodic Gradient Impedance Matching - Wu, Fei; Zhang, Xiao; Ju, Zegang; Zhao, Jiang; Hu, Man; Gao, Mingyuan; Luo, Jun; Pu, Huayan (Frontiers in Materials, 2022)
Ultra-broadband sound absorption with periodic gradient impedance matching is of great concern in the research of acoustic materials. This study investigates the impedance matching of composite acoustic metamaterials comprising micro-perforated plates (MPPs) and subsequent Fabry–Pérot(FP) channels. Based on the impedance matching theory, ultra-broadband sound absorption has been realized through a design with 36 channels whose thickness is only 50 mm. Also, the average sound absorption coefficient of 88% and an absorption frequency bandwidth (490–4000 Hz) can be achieved by preserving the matching impedance. Furthermore, by changing the thickness of the perfect absorber being 100 mm, the average sound absorption coefficient can reach greater than 90% in the frequency range of 250–4500 Hz. The proposed structure is validated analytically and experimentally. This work can help with designing and improving the method of acoustic metasurfaces and especially have the potential in ultra-broadband sound absorber designs.